Nervous laughter: Comedy, disabilities and the reconstitution of space. (1st March 2019) - Nevárez Araújo, Daniel
Comedy has historically assigned a position of Different (to use Susan Wenll's term, which substitutes for the more stigmatizing term Other) to those it uses as the butt of the joke, or rather it makes jokes at the expense of those deemed different. As a matter of fact, a cursory look at some comedic texts reveals that, quite often, comedy amplifies the social positionality of the excluded. We laugh at specific identities, bodies, tendencies and even traits seen as making the object of the joke inferior. Disabled people consistently find themselves in that position as a particular identity or type of body that serves as the object of jokes. That said, over the last decade, there has been an increase in people with disabilities engaging in and creating their own comedic material, particularly of the stand-up variety. Disabled comedians demand a reassessment of the rules of propriety, tact and respectability in comedic spaces. Thus disabled comedians elicit nervous laughter from their audiences as the audiences grapple with a body and identity they greatly ignore out in the open social landscape and are now invited to laugh with.